Factors predicting resilience among caregivers of people with chronic illness: A cross-sectional study of Thai caregivers - Jeeraporn Kummabutr; Natthapat Buaboon; Siriluck Keawsriwong (Belitung Nursing Journal)
Background: Millions of adults in Thailand serve as caregivers, facing significant public health challenges related to caregiver burden and well-being. Resilience is linked to better caregiver outcomes, yet the predictors of resilience are not fully understood.